2022
DOI: 10.1001/jamanetworkopen.2022.16913
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicaid Expansion With Emergency Department Visits by Medical Urgency

Abstract: Key Points Question Is Medicaid eligibility expansion associated with changes in emergency department (ED) visits based on the medical urgency of the conditions? Findings In this cross-sectional study of 80.6 million ED visits across 4 US states, ED visits per 1000 population decreased for states that expanded Medicaid compared with states that did not. This decrease was associated with decreases in ED visits for less-emergent or nonemergent conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…Although Giannouchos et al found encouraging patterns of ED use, other studies have found the opposite. In particular, a 2019 study by Garthwaite et al, which also used Healthcare Cost and Utilization Project data, but included 20 states and all ED visits (both outpatient ED visits as well as those leading to inpatient admission), found that ED use for deferrable conditions increased in expansion states relative to nonexpansion states, whereas those for nondeferrable conditions did not.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…Although Giannouchos et al found encouraging patterns of ED use, other studies have found the opposite. In particular, a 2019 study by Garthwaite et al, which also used Healthcare Cost and Utilization Project data, but included 20 states and all ED visits (both outpatient ED visits as well as those leading to inpatient admission), found that ED use for deferrable conditions increased in expansion states relative to nonexpansion states, whereas those for nondeferrable conditions did not.…”
mentioning
confidence: 89%
“…The investigators found that Medicaid expansion was associated with a significant reduction in overall ED use by 4.7 visits per 1000 population. 3 Furthermore, this reduction was associated largely with changes in the subgroups of ED visits that are potentially avoidable, with greater decreases noted for the least severe conditions that are likely to be most avoidable and smaller decreases for higher severity conditions. Visits classified as nonemergent decreased by 1.5 visits per 1000 population, those classified as primary care treatable declined by 1.1 visits per 1000 population, and those classified as emergent, but potentially preventable declined by 0.3 visits per 1000 population (all statistically significant declines).…”
mentioning
confidence: 99%
See 3 more Smart Citations